Non-Face-to-Face Services in Neurologic Care - Grouse, Carrie K. (Seminars in Neurology, 2025)
Neurologists in ambulatory settings struggle with low appointment availability and increased work related to patient care outside of clinic visits. Neurologists can better meet these demands using asynchronous or non-face-to-face care options. Specific billing codes allow reimbursement for work neurologists are already doing to care for their patients between visits. This includes care delivery over patient portal messages (e-visits), asynchronous consultations through the electronic health record (EHR) system requested by providers for their patients with neurologic issues (eConsults), care coordination and record review outside of clinic visits (prolonged service for non-face-to-face care outside of the date of service and transitional care management), and analyzing data from new technologies and devices for patient diagnosis and therapeutic monitoring (remote patient monitoring). Artificial intelligence shows promise to improve how neurologists deliver asynchronous care. More seamless incorporation of asynchronous care options in the EHR and clinic templates will ultimately be necessary to improve neurologists' efficiency and work–life balance.
Keywords: asynchronous; non-face-to-face; e-visit; eConsult